Decision Support System Model for College Kartu Indonesia Pintar (KIP) Scholarship Recipients Using the C4.5 Decision Tree Method and Simple Additive Weighting (SAW) - Hadi, Nofiar; Rizkiawan, M. Asep; Moedjiono, Moedjiono; Nuroji, Nuroji (Institut Teknologi dan Bisnis Bina Sarana Global, 2024)
The KIP-Kuliah Scholarship is an Indonesian government program that is used to help high school students (SMA) or equivalent who are less capable but have academic potential in financing education in college. In this study, the problem limitation or scope of research is at Prof. DR. HAMKA Muhammadiyah University College in the Management Study Program. In each year the selection of scholarship acceptance often changes criteria, because of the frequent changes in scholarship criteria each year users often experience problems in selecting KIP-Kuliah scholarship recipients. Decision Support System (SPK) is a solution to assist in decision making. The purpose of this research is to assist in decision making in determining scholarship recipients in accordance with existing criteria. The method used in this research is using Decision Tree C4.5 to determine the weight of the KIP-Kuliah scholarship criteria and the Simple Additive Weighting (SAW) method is used to determine the ranking of scholarship recipients. In this study, researchers used 3 criteria, namely the amount of parents' income, the number of dependents, and the interview test scores. The results of the analysis of the calculations using the Decision Tree C4.5 and Simple Additive Weighting (SAW) methods and the results of the selection of college KIP scholarships consisting of the criteria for the amount of parents' income, the number of dependents and the interview test, the 12 students who deserve college KIP scholarships are students who get the highest preference scores, namely M11, M3, M6, M4, M14, M1, M5, M12, M10, M2, M7, and M9. In conclusion, the use of a Decision Support System with the Decision Tree C4.5 and Simple Additive Weighting (SAW) methods is effective in helping determine the recipients of the KIP-Kuliah scholarship in accordance with predetermined criteria.